Shaping Student’s Career Aspirations through Parenting: A Study of Parenting Styles for Public Secondary School Students in Nairobi City County, Kenya - Samuel , Mercy Igoki Samuel; Changwony , Dinah (African Journal of Education,Science and Technology (AJEST), 2021)
Parenting styles is the manner in which the parents instill discipline in their children with an aim of influencing their behaviour. Different types of parenting styles have varied characteristics with relative effects on the general behaviour of children. The style of parenting adopted in different homes affect the children’s disposition. This can facilitate the development of a child or be detriment of his or her academic career. This paper is drawn on a study that sought to explore the relationship between students’ career aspirations and different parenting styles among students in public secondary schools in Nairobi City County. The study was informed by the Family Systems Theory. Descriptive survey research design approach was used for quantitative data analysis where a sample of 60 public secondary schools drawn from Nairobi City County was used. Students and guiding and counseling teachers formed the target respondents. The findings of the study show that the discipline and academic achievement of the students largely depend on the parenting style adopted by their parents. While some parenting styles such as authoritative promote good behavior in children, others like authoritarian promote dysfunctional behaviour negatively impacting on the students’ career aspirations. The study recommends parents/guardian not to have very high expectations of students. The findings of this study are significant to school Principals in that they will be in a position to provide vital background knowledge to apply in the context of family therapy. In this case, they will be able to pass similar knowledge to parents/guardians about the crucial role that they play consciously or unconsciously in shaping the behavior of their children, relating either to children's socialization or scholastic performance.